Introduction to Biophysical Methods for Protein and Nucleic Acid Research - Glasel, Jay A; Ed. Deutscher, Murray P; Ed (Academic Press, 1995)
The first of its kind, Introduction to Biophysical Methods for Protein and Nucleic Acid Research serves as a text for the experienced researcher and student requiring an introduction to the field. Each chapter presents a description of the physical basis of the method, the type of information that may be obtained with the method, how data should be analyzed and interpreted and, where appropriate, practical tips about procedures and equipment. Key Features * Modern Use of Mass Spectroscopy * NMR Spectroscopy * Molecular Modeling and Graphics * Macintosh and DOS/Windows 3.x disks.